Adolescent development and sexual behavior: II. Sexual education proposals - Di Pietro, Maria Luisa; Lucattini, Adelia (Medicina e Morale, 1992)
The need for sexual education for adolescents emerges from the analysis of their sexual behavior and this is the only way to avoid the risks for the individual and for society that could derive from this behavior. In the light of the present pedagogical trends this paper tries to identify the most suitable educational strategy for the needs and characteristics of adolescent psycho-sexual development, while also indicating the qualities that the educators (parents and teachers) should have in order to be able to deal with these delicate problems.